Surgery in the Revolutions of 1897 and 1904 - Bergalli, Luis (Cirugía del Uruguay, 1980)
The author refers in this article the history of surgery and sanitary assistance in Uruguay, during the civil wars of 1897 and 1904. The development of surgery and the performance of surgeons in both struggles are related.